The role of small mammals for incidence of zoonotic diseases under climate change - Palo, R Thomas; Ahlm, Clas (Institutionen för naturvetenskap, teknik och matematik, 2009)
Animal-borne diseases are likely to be affected by climate change. It is of interest to analyse sensitivity of reservoir species to climate change and how changes in their ecology would affect transmission of zoonoti diseases to man. Elevated temperature in northern hemisphere may have direct effects on reservoir species by greater survival and hence generally higher population densities. Further, warmer climate may make certain key habitats more beneficial for replication and possibly greater transfer of disease. On the other hand, animal responses to climate change may vary among species and changes in their ecology causing increased variability in population size or dependence of timing with certain food resources may adversely affect reservoir species. We analysed the number of human disease cases of tick borne encephalitis (TBE), tularaemia and hantavirus in norhern Sweden in relation to population size of their most common reservoirs, the mountain hare, European hare and the bank vole. We also analysed the effect by a common predator the red fox and we used the NAO index as a proxy for climate variations. The results show that hantavirus infection in man is more dependent on the population density of reservoirs than on the climate variable. In case of tularaemia, we found a more complex ecological situation that may be climate driven.We conclude that the outcome of warmer climate may vary among species but that species adapted to northern winter conditions may be particularly sensitive to climate change. zoonoser